ANALYSIS OF COLIFORM BACTERIA IN DUG WELL WATER - Yustati, Eva (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2024)
In Indonesia, in rural and urban areas, you can find a lot of dug wells, because in general people use a lot of dug wells, because dug wells are relatively easy and cheap to make. However, dug wells have a very high risk of pollution in the form of physical, chemical and biological pollution. Water and health are two things that are interconnected. If the quality of the water consumed by the public is contaminated by coliform bacteria and E coli bacteria, it can cause diseases including diarrhea. This research aims to determine the relationship between the distance of the septic tank and the physical condition of the dug well on the number of coliform bacteria in the dug well water using the Cross Sectional method. Samples were taken using a simple random sampling technique with a total sample of 89 dug wells.  The data obtained were analyzed using the Chi-Square test. Univariate analysis. The presence of coliform bacteria was 31.5%, 65.8% absent, septic tank distance did not meet the requirements, 43.8% met the requirements, 56.2%, the physical condition of the dug well met the requirements. 36.0% requirements, 60.0% eligible. Bivariate analysis of septic tank distance obtained a value of 0.000, the physical condition of the dug well had a p value of 0.000. The conclusion was that there was a significant relationship between the distance of the septic tank and the physical condition of the dug well and the presence of coliform bacteria.